MODERN APPROACHES TO ENSURING THE QUALITY OF EDUCATION - Saidova Khilolakhan Rashidjonqizi (International Journal of Innovations in Engineering Research and Technology, 2022)
This article describes international experiences and approaches in ensuring the quality of education, the application of world experience in the development of higher education. Also, international quality assessment models and issues of attestation and accreditation, which are considered an important quality assurance mechanism, are covered in detail.